Social capital analysis in sustainability of Batik Tulis Lasem and community empowerment in Rembang - Winarti, Eni; Prajanti, Sucihatiningsih Dian Wisika; Brata, Nugroho Trisnu (Universitas Negeri Semarang, 2024)
This writing aims to empower the community with a social-humanities perspective. The development of local economic potential in the community is a form of community empowerment that can increase job opportunities. In addition to providing employment opportunities for the economic development community, researchers use qualitative methods that produce qualitative descriptive data through observation techniques and in-depth interviews to explore data on community empowerment based on social capital in Lasem batik business actors to increase community empowerment and identify the sustainability of Lasem's batik business in Rembang Regency. The results showed that: social capital has a very important role in the community, especially in the sustainability of the Lasem batik writing business, the business continuity of Lasem batik business owners in Rembang Regency includes capital sustainability, human resource sustainability, production sustainability, distribution sustainability, and consumption sustainability, obstacles and support for the sustainability of the Lasem batik writing industry in order to Business continuity and community empowerment can run well.